TI_GERICHTE 52.2006.83 vom 12. Juni 2006 , Demolizione di un muro a secco e di una serra fuori della zona edificabile - TI Tribunale d'appello (2006)
Demolizione di un muro a secco e di una serra fuori della zona edificabile